2015
DOI: 10.18632/oncotarget.6161
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic TLR4 signaling is activated by LPS from digestive tract during SARA, and epigenetic mechanisms contribute to enforced TLR4 expression

Abstract: Subacute ruminal acidosis (SARA) is known to trigger a systemic inflammatory response that is possibly caused by the translocationof lipopolysaccharides (LPS) from the gastrointestinal tract into the bloodstream. The aim of this study is to investigate this causal relationship between the increases of circulating LPS and liver inflammation. Here we found that SARA goats exhibited significantly increased LPS concentrations in both the rumen and portal vein. The livers of these goats exhibited increased mRNA con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
4
41
0
Order By: Relevance
“…Taken together, the distinctive base of above mentioned facts firmly suggests that LPS triggered the activation of TLR4 signaling, resulting in an inflammatory response in the uterus of goats suffering from SARA. Overwhelmingly, the data in the current study indicate that LPS triggers the TLR4-NF-κB signaling pathway, in accord with an earlier study (Chang et al, 2015). The present study found that SARA increased the mRNA expression and protein concentrations of NF-κB in the uterus of TG goats.…”
Section: Fig 3: Uterine Gene Expression Profile Analysis With Qrt-pcrsupporting
confidence: 92%
See 1 more Smart Citation
“…Taken together, the distinctive base of above mentioned facts firmly suggests that LPS triggered the activation of TLR4 signaling, resulting in an inflammatory response in the uterus of goats suffering from SARA. Overwhelmingly, the data in the current study indicate that LPS triggers the TLR4-NF-κB signaling pathway, in accord with an earlier study (Chang et al, 2015). The present study found that SARA increased the mRNA expression and protein concentrations of NF-κB in the uterus of TG goats.…”
Section: Fig 3: Uterine Gene Expression Profile Analysis With Qrt-pcrsupporting
confidence: 92%
“…Moreover, it was observed that high concentrate feeding increased the free LPS level in the rumen; LPS subsequently translocated into the blood stream with the possible major site of LPS translocation into the blood stream being the intestines (Khafipour et al, 2009). Recently, Chang et al (2015) reported that a harmful feature of high grain diet-induced SARA is the induction of liver inflammation. The high rise in circulating LPS triggers inflammation that in turn stimulates extensive TLR4 signaling and ultimately elevates the expressions of innate immune genes and enhances the secretion of pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…According to our results, the increased expression of TLR4 indicated that TLR4 recognized the LPS and triggered the inflammatory pathway [9, 38]. Identification of inflammatory-stimuli by the innate immune system is organized by PPR that identify external stimuli for example pathogen associated molecular patterns (PAMPs) [39].…”
Section: Discussionmentioning
confidence: 99%
“…The persistent consumption of a HC diet by dairy animals enhances the production of organic acids and significantly results in a decline in pH values of the rumen and intestine [57]. This decrease in pH due to excessive high concentrate diet [8] may affect the alterations of the type of fermentation [9] and the structure of the microbes in the rumen [10, 11]. Moreover, the decline in pH also perturbs the balance of microbial population in the rumen causing substantial release of free endotoxin (lipopolysaccharide, LPS) from gram-negative bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…Generally known for its proinflammatory properties, NF-κB is also an important antiapoptotic factor (48,49). LPS activation and TNF collectively lead to increased TLR4 expression, proinflammatory cytokine production, and inflammation, on the one hand, and NF-κB activation and cytoprotection on the other (48).…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonmentioning
confidence: 99%